Company Recycling Practices in Bali and Their Role in Sustainable Waste Management - Lawrence, Nasya Bunnyrose; Yuliastuti, Yuliastuti (Jurnal Sains Sosio Humaniora, 2026)
Recycling is an important component of sustainable waste management, yet in many organizational settings it remains a voluntary practice rather than an established operational requirement. This study examines company recycling practices in Bali and identifies organizational and policy factors that may support recycling as a routine practice. Using a descriptive survey design, data were collected from 37 respondents associated with company-related environments in Bali, including employees, business owners, customers, students, parents, and other stakeholders. The questionnaire examined current recycling practices, perceived company responsibility, awareness of local recycling programs, barriers, support needs, and willingness to support company recycling policies. The findings show strong normative support for recycling: 81.1% of respondents believed that companies have a responsibility to recycle, and 94.6% considered recycling very important for the environment. However, recycling was not yet consistently institutionalized. A total of 40.5% reported that recycling was practiced in their company-related setting, while another 40.5% reported that it was practiced only sometimes. The main barrier was limited access to nearby recycling facilities, identified by 45.9% of respondents. Respondents also emphasized the need for practical support, with 54.1% identifying free or easier access to recycling facilities as an important enabling factor. The study concludes that company recycling in Bali requires more than environmental awareness. The study contributes to organizational sustainability research by clarifying how normative support, operational capacity, and external policy support interact in shaping company recycling practices.